Bidentate Aromatic Thiols on Gold New Insight Regarding the Influence of Branching on the Structure, Packing, Wetting, and Stability of Self-Assembled Monolayers on Gold Surfaces - Rittikulsittichai, Supachai (Langmuir : the ACS journal of surfaces and colloids, 2017)
A series of 2-phenylpropane-1,3-dithiol derivatives with single (R1ArDT), double (R2ArDT), and triple (R3ArDT) octadecyloxy chains substituted at the 4-, 3,5-, and, 3,4,5-positions, respectively, on the aromatic ring were synthesized and used to form self-assembled monolayers (SAMs) on gold. Insight into the relationship between the surface chain and headgroup packing densities was investigated by varying the number of surface chains for the bidentate adsorbates in these monolayers. Characterization of the resulting SAMs using ellipsometry, X-ray photoelectron spectroscopy, polarization modulation infrared reflection-absorption spectroscopy, and contact angle goniometry revealed that the tailgroups become more comformationally ordered and more densely packed as the number of alkyl chains per adsorbate was increased. Conversely, the molecular packing density (i.e., number of molecules per unit area) decreased as the number of alkyl chains per adsorbate was increased. Of particular interest, the desorption profiles obtained in isooctane at 80 °C suggested that the bidentate adsorbate with the most densely packed alkyl chains, R3ArDT, was significantly more stable than the other SAMs, producing the following relative order for thermal stability for the dithiolate SAMs: R3ArDT > R2ArDT > R1ArDT